Revitalisasi Pancasila: Epos dan Kontroversi di Balik Undang-Undang Cipta Kerja - Lestari Wulandari S (LPPM Universitas Ekasakti Padang, 2023)
This article explores the epic and controversial dimensions in the context of Pancasila Revitalization as revealed through an in-depth study of the Job Creation Law. The revitalization of Pancasila is the primary basis for responding to social and economic changes in the contemporary era, which are reflected in the latest legal reforms. Through an interdisciplinary approach, this article outlines the journey of the Pancasila Revitalization epic, revealing its critical role in shaping the national legal structure. Not only as an ideological doctrine, Pancasila is the conceptual basis for designing and implementing the Job Creation Law. However, this part of the epic also involves several controversies arising from various societal levels. The controversy discussion includes multiple perspectives, ranging from the economic impact to the social tensions. This article explores the layers of complexity that arise from the combination of the noble ideals of Pancasila and the reality of its implementation in the Job Creation Law. By highlighting crucial points, this article aims to provide a deeper understanding of the relationship between Pancasila, current legislation, and societal dynamics. In this way, readers are invited to reflect on the significance of the Revitalization of Pancasila in shaping the future direction of law and justice in Indonesia.